Faktor yang Berhubungan dengan Motivasi Kerja Pegawai di Dinas Kesehatan, Pengendalian Penduduk dan Keluarga Berencana Kabupaten Marowali - Yatrin Iftalis Tansala; Sukirno Kasau; Akmal Novrian Syahruddin (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Employee work motivation is a crucial element in determining the quality of public services, especially in the health sector. This study aims to analyze factors related to employee work motivation at the Health, Population Control, and Family Planning Office of Marowali Regency. This study uses a quantitative approach with a cross-sectional design. The sample consisted of 39 respondents selected through the purposive sampling method. The research instrument is in the form of a structured questionnaire, and data analysis is carried out bivariously using the chi-square test and Fisher's Exact Test if the test assumptions are not met. The results showed that the work environment did not have a significant relationship with work motivation (p = 0.129). In contrast, the benefits variable showed a significant relationship (p = 0.009), and workload also had a significant effect on work motivation (p = 0.004). These findings indicate that employees' work motivation is significantly influenced by benefits and workload factors, while the work environment does not have a significant impact. The practical implication of this study is the need for managerial attention to a fair incentive system and a proportionate distribution of workload to increase employee work motivation. Increasing work motivation is expected to encourage the efficiency and effectiveness of public services in the health sector. This research contributes to the development of evidence-based human resource policies in the regional health service sector.